A two-point study of parental perception of digital technology in Croatian preschool children - Kotrla Topić, Marina (Array, 2020)
To get a better understanding of the parental perception of digital devices used by preschool children in Croatia, as well as their expectations and mediation strategies, we report the findings from a qualitative study with two measurement points. At the first point, five families with children aged 6 to 7 were interviewed at their homes, where they provided information on how their children engage with new technologies, how such technologies are perceived by different family members and how parents manage their children’s use of digital technology. A year and a half later, the same families were interviewed again, in a similar manner, focusing on the changes which happened in that period, as reported by the parents. Results show that parents find digital technology important and beneficial for children’s cognitive and emotional development, but they fear possible negative consequences of its use. Most often, they use restrictive mediation. A year and a half later, parents also express the need for more educational support when it comes to mediating their children’s interaction with digital technology.